Survey parameters for detecting 21-cm-Ly α emitter cross-correlations with the Square Kilometre Array. (22nd June 2018) - Hutter, Anne; Trott, Cathryn M; Dayal, Pratika
Abstract: Detections of the cross-correlation signal between the 21 cm signal during reionization and high-redshift Lyman-α (Ly α) emitters (LAEs) are subject to observational uncertainties which mainly include systematics associated with radio interferometers and LAE selection. These uncertainties can be reduced by increasing the survey volume and/or the survey luminosity limit, i.e. the faintest detectable Ly α luminosity. We use our model of high-redshift LAEs and the underlying reionization state to compute the uncertainties of the 21-cm-LAE cross-correlation function at $z$  ≃ 6.6 for observations with SKA1-Low and LAE surveys with Δ$z$ = 0.1 for three different values of the average inter-galactic medium (IGM) ionization state (⟨χH i ⟩ ≃ 0.1, 0.25, 0.5). At $z$  ≃ 6.6, we find SILVERRUSH type surveys, with a field of view of 21 deg 2 and survey luminosity limits of L α ≥ 7.9 × 10 42  erg s −1, to be optimal to distinguish between an IGM that is 50 , 25 , and 10 per  cent neutral, while surveys with smaller fields of view and lower survey luminosity limits, such as the 5 and 10 deg 2 surveys with WFIRST, can only discriminate between a 50  and 10 per  cent neutral IGM.